2018
DOI: 10.1093/jas/skx019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing sow diets with fermented corn and soybean meal mixed feed during lactation on the performance of sows and progeny

Abstract: In the present study, two experiments were performed to study the effects of feeding fermented corn and soybean meal mixed feed (FMF) with Bacillus subtilis and Enterococcus faecium to lactating sows on the performance of the sows and their progeny. In experiment 1, 60 sows were allocated to the following three dietary treatments: 1) sows fed a corn and soybean meal basal diet (control) from day 3 before parturition to weaning, 2) sows fed a diet with 7.5% FMF, and 3) sows fed a diet with 15% FMF. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…Nutrient digestibility was calculated as described by Wang et al [ 22 ]. For the digestive enzyme activity of duodenum and jejunum determination, the mucosa of the duodenum and jejunum were collected and homogenized by adding sterile 4% saline solution to prepare 10% (W:V) homogenates.…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient digestibility was calculated as described by Wang et al [ 22 ]. For the digestive enzyme activity of duodenum and jejunum determination, the mucosa of the duodenum and jejunum were collected and homogenized by adding sterile 4% saline solution to prepare 10% (W:V) homogenates.…”
Section: Methodsmentioning
confidence: 99%
“…The sows’ feed intake during the experiment was measured. Sows’ backfat was determined following our previous study (Wang et al ., 2018a). The constipation rate of sows and diarrhoea incidence of piglets were measured from parturition to weaning.…”
Section: Methodsmentioning
confidence: 99%
“…Lactation period of sows is an important stage of swine breeding (Tokach et al ., 2019). Several studies reported the beneficial effects of FF on the performance of lactating sows and their offspring (Demeckova et al ., 2002; Shen et al ., 2011; Wang et al ., 2018a). However, whether FF ameliorates the immune status and gut microbiota of lactating sows and the effective composition of FF is probiotics remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Milk composition can be altered by maternal (gestational and lactational) diets. The changes in milk composition can ultimately impact growth, immunity, and gut health of offspring [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and so investigations of how supplementation of sow’s diets during gestation and lactation impact piglet performance are receiving considerable attention [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%